Review on liquid chromatographic analysis of colchicine in the forensic and medical perspective - Krishna, Rohith; Shivankar, Bhavana (Toxicologie Analytique et Clinique, 2021)
Colchicine is a tricyclic alkaloid extracted from the family of plants called Colchicaceae. Colchicine is pharmacologically active and works as an anti-mitotic agent. The alkaloid has a narrow therapeutic index, and a slight increase in colchicine concentration can lead to toxicity, and an overdose can be fatal to the individual. This nature of the alkaloid has made the scientific community interested in the analysis of colchicine. This critical review mainly comprises an analytical overview of the extraction and the liquid chromatographic (LC) analysis of colchicine in the field of forensic and medical toxicology. The prominent extraction techniques, detectors, and liquid chromatographic parameters favorable for colchicine estimation have been discussed in this paper. This review has covered the relevant research works within a timeline of two decades based on the scope of the literature and the scientific importance.